Advanced treatment techniques for the manual therapist : neck - Muscolino, Joseph E. (LWW in touch series, 2013)
"As the field of massage therapy has gained greater acceptance, its role within the health field has increased commensurately. For this reason, there is a growing need for advanced treatment techniques that are oriented toward clinical rehabilitation of clients who present with musculo-skeletal conditions. The purpose of this book is to present an array of these advanced treatment techniques that can be used by the massage therapist and other manual therapists. Advanced Treatment Techniques for the Manual Therapist: Neck is designed to be used by the practicing therapist who wants to learn advanced techniques that likely were not taught during his or her training at school. This book is also designed to comfortably fit into the curriculum of a massage therapy or other bodywork school that desires to teach these techniques, whether it is within the core curriculum or within the continuing education offerings. Note that what is and is not within the scope of practice of a massage therapist or other manual therapist varies from state to state, and occasionally varies from one town, city, county, or province to another. It is the responsibility of the practicing therapist to make sure that he or she is practicing legally and employing treatment techniques that are within the scope of his or her license or certification"--Provided by publisher